Phylogeography of the reed frog Hyperolius castaneus (Anura: Hyperoliidae) from the Albertine Rift of Central Africa: Implications for taxonomy, biogeography and conservation - Greenbaum, Eli; Sinsch, Ulrich; Lehr, Edgar; Valdez, Federico; Kusamba, Chifundera (Zootaxa, 2013)
We examine the systematics of multiple populations of the Albertine Rift endemic amphibian Hyperolius castaneus, which currently incorporates four subspecies. Standard morphometric data were analyzed with principal components analyses and analyses of covariance. Phylogenetic analyses of two mitochondrial (16S, cyt b) and one nuclear (RAG1) genes were analyzed from 41 samples representing three subspecies. Results indicated some significant morphometric differences between the nominate subspecies H. c. castaneus and the Itombwe Plateau subspecies H. c. constellatus, and phylogenetic analyses of molecular data recovered these taxa as reciprocally monophyletic groups. We recognize these two allopatric populations as recently diverged, but distinct species, H. castaneus and H. constellatus. The subspecies H. c. submarginatus from the Kabobo Plateau is transferred to the synonymy of H. constellatus, but the status of the unsampled subspecies H. c. rhodogaster, described from mid-elevations of the western Itombwe Plateau, remains problematic. The phylogeographic pattern of our study resembles some, but not all, Albertine Rift vertebrates that have been examined with molecular data. Hyperolius constellatus is restricted to the Itombwe and Kabobo plateaus, which are of special conservation concern because of high levels of amphibian diversity and endemism, and multiple threats from deforestation, mining activities and road construction.